Kajian Teknologi Mina Padi di Rawa Lebak di Kabupaten Batanghari Provinsi Jambi - Julistia Bobihoe; Nur Asni; Endrizal Endrizal (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
Mina rice is a technology that combines fish farming with rice cultivation. This system has several advantages such as: farmers will get additional income from fish without reducing the incomes of rice, increasing rice production, improve efficiency and productivity of the land, the rice plants become more controlled and meet the needs of animal protein. The assessment carried out by an integrated crop management (ICM) lowland swamp rice. The assessment was conducted in the village of Rantau Kapas Tuo District Muaro Tembesi Batanghari regency of Jambi Province in April and August 2012. The assessment aims to determine the level of growth and yield of rice and fish on rice farming mina. Assessment carried out on two hectares of land by applying some technology components include: the selection of fish seed, nursery, land preparation, manufacture caren/trench planting rice, fish stocking, fertilization, water management, fertilization, weeding, maintenance of fish, control crop pests and diseases. New varieties (VUB) rice used is Inpara 3 seed and fish used is Tilapia. The study showed that rice production is 6.85 t/ha and survival rate of fish was 75%. The assessment is seen that by applying mina rice cultivation with rice integrated crop management (ICM) earned income of Rp 14.11 million (B/C ratio 1.1) and the non ICM and an income of Rp 2.485 million (B/C Ratio 0.4).